Crystal sediment profile in the urine of public transportation drivers on route 2 in Kupang city - Ledoh, Yaksem Yohanis; Djuma, Agustina Welhelmina; Kapitan, Lely Adel Violin (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: Drivers have a profession that requires prolonged sitting, leading to the release of bone calcium into the bloodstream, which can trigger the formation of urinary stones or nephrolithiasis. Urinary stone (nephrolithiasis) is a condition where stones form in the urinary tract. Objectives: The aim of this study was to describe the crystal sediment profile in the urine of public transportation drivers on Route 2 in Kupang City. Materials and Methods: This descriptive study involved 16 public transportation drivers on Route 2 in Kupang City as research subjects. Data were collected through interviews.  Results: The results showed the presence of various crystals in the urine sediment, including Calcium Oxalate crystals (25%), Calcium Carbonate crystals (18.75%), Uric Acid crystals (12.5%), and Amorphous crystals (6.25%).  Conclusions: Based on the characteristics and habits of the respondents, it was found that frequent urinary retention, drinking less than 1 liter of water per day, and consuming supplemented or carbonated drinks were the three main factors affecting urine sedimentation in public transportation drivers on Route 2 in Kupang City.